2018
DOI: 10.1113/jp277122
|View full text |Cite
|
Sign up to set email alerts
|

Human brain blood flow and metabolism during isocapnic hyperoxia: the role of reactive oxygen species

Abstract: Key points It is unknown whether excessive reactive oxygen species (ROS) production drives the isocapnic hyperoxia (IH)‐induced decline in human cerebral blood flow (CBF) via reduced nitric oxide (NO) bioavailability and leads to disruption of the blood–brain barrier (BBB) or neural‐parenchymal damage. Cerebral metabolic rate for oxygen (CMRnormalO2) and transcerebral exchanges of NO end‐products, oxidants, antioxidants and neural‐parenchymal damage markers were simultaneously quantified under IH with intrave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 60 publications
(160 reference statements)
5
53
0
2
Order By: Relevance
“…Other human studies have indicated that hyperoxia induces cerebral vasoconstriction as a consequence of altered regional nitric oxide potentially contributing to the stress diathesis under anaesthesia. 44 Also of note are findings of altered CVR with increasing age 45 and with signs of dementia in the elderly 46 or in patients with biomarkers such as APO4ε related to early onset Alzheimer's disease. 47 The identification of regional 'intracranial steal' or 'blue brain' on the BOLD images with a CO2 ramp protocol is increasingly being used to establish the need for and measure results from revascularization with superficial temporal artery to middle cerebral artery (STA-MCA) anastomoses in patients with severe intracranial vascular compromise.…”
Section: Discussionmentioning
confidence: 99%
“…Other human studies have indicated that hyperoxia induces cerebral vasoconstriction as a consequence of altered regional nitric oxide potentially contributing to the stress diathesis under anaesthesia. 44 Also of note are findings of altered CVR with increasing age 45 and with signs of dementia in the elderly 46 or in patients with biomarkers such as APO4ε related to early onset Alzheimer's disease. 47 The identification of regional 'intracranial steal' or 'blue brain' on the BOLD images with a CO2 ramp protocol is increasingly being used to establish the need for and measure results from revascularization with superficial temporal artery to middle cerebral artery (STA-MCA) anastomoses in patients with severe intracranial vascular compromise.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the brain's O 2 supply is so delicate, walking the tightrope between too much or too little of this rocket fuel, it would seem intuitive for evolution to favour feedback mechanisms capable of sensing subtle changes in blood O 2 concentration and transmitting signals to the cerebrovasculature coupling local cerebral O 2 delivery to tissue metabolic demand. The new information presented by Mattos et al (2019) adds to an emerging, albeit limited, body of human evidence, indicating that free radicals may well fulfil such a role in preserving cellular O 2 homeostasis.…”
mentioning
confidence: 97%
“…The new information presented by Mattos et al . () adds to an emerging, albeit limited, body of human evidence, indicating that free radicals may well fulfil such a role in preserving cellular O 2 homeostasis.…”
mentioning
confidence: 99%
See 2 more Smart Citations